Modeling and Force Analysis of an Electrothermal Micro Gripper with Amplification Compliant Mechanism - Dang, Bao Lam; Nguyen, Tuan Khoa; Nguyen, Dang Thuan; Pham, Hong Phuc (Old Journal, 2017)
This work reports a novel design of a micro gripper, in which V-shaped electrothermal actuators are used to create gripping force and a compliant mechanism is integrated to amplify displacements of the actuators. The gripper is designed to handle micro samples of various sizes from 5 µm to 50 µm by applying appropriate driving voltages. Those voltages are ranged from 5 V to 25 V, which are relatively low in comparison with driving voltages of the electrostatic micro grippers. The compliant mechanism with amplifying ratio 5.2, arranged between the actuators and the jaws, is aimed to compensate small strokes of the actuators. Simulation by Finite-Element Analysis has also been carried out to confirm results of the theoretical calculation and designing process. The micro gripper can be implemented in micro devices such as micro robots or micro assembling systems, in which it can perform gripping and transporting tasks.